“I learned a lot about me as a person”: University students’ development as non-formal education professionals - Simpson, Amber; McCann, Jada; Murtaugh, Diana; Miroff, Laurie E. (Frontiers in Education, 2025)
IntroductionThe role of non-formal educational professionals has implications for the growth and development of the children they interact with. This group of professionals includes university students who volunteer their time in educational and youth-service organizations.MethodsIn this collective case study, we utilized Cultural-Historical Activity Theory to (a) understand how undergraduate and graduate students negotiated their development as a non-formal educational professional within an afterschool program and (b) consider how contradictions influenced their growth as educators, if at all. Three forms of data were collected from 10 graduate and undergraduate students as they volunteered their time as an educator in a 10-week afterschool program in partnership with two rural middle schools.ResultsResults highlighted shared contradictions among university students, such as lack of content knowledge and being viewed as friend versus being viewed as an educator, as they individually and collectively reflected upon their development and growth as non-formal educators within the afterschool program. Results also underscored how being a part of the afterschool program and reflecting on practice supported only some of the university students’ initial goal(s) for volunteering their time.DiscussionWe conclude with implications of this study for universities to consider in supporting the professional growth and development of their students as active learners and future educational professionals.